Rancang Bangun Game 3D Pertahanan Kerajaan Bowontehu - Mekel, Weliam J.; Sompie, Sherwin R.U.A.; Sugiarso, Brave A. (Jurnal Teknik Informatika, 2019)
Abstract - Games are a medium of entertainment that is in great demand by the public at this time, including by children. Besides being a medium of entertainment, games can also be used as a medium for children's learning. This type of game is called an educational game. By using educational game media, the learning process will be more fun. The aim of this game is to Generate 3D Defense Game of Bowontehu Kingdom. The method used is the MDLC (Multymedia Development Life Cycle) method which has 6 stages. Based on the results of the questionnaire obtained, 50% of respondents answered the existence of the kingdom of Bowontehu in the city of Manado,after playing 90% of the Respondents Answered already knew of events in the Kingdom of Bowontehu. In this study there are some shortcomings and need to be reviewed in the form of subsequent developments that can be used on other platforms. Keywords — Adobe Fuse, Education Games, Game 3D, Unity 3D. Abstrak – Game adalah media hiburan yang sangat diminati oleh masyarakat saat ini, termasuk oleh anak-anak. Selain sebagai media hiburan, game juga dapat digunakan sebagai media untuk belajar anak-anak. Jenis permainan ini disebut permainan edukatif. Dengan menggunakan media game edukasi, proses pembelajaran akan lebih menyenangkan. Tujuan dari game ini adalah untuk Menghasilkan Game Pertahanan 3D dari Kerajaan Bowontehu. Metode yang digunakan adalah metode MDLC (Multymedia Development Life Cycle) yang memiliki 6 tahap. Berdasarkan hasil kuesioner yang diperoleh, 50% responden menjawab keberadaan kerajaan Bowontehu di kota Manado, setelah bermain 90% dari Responden Dijawab sudah mengetahui peristiwa di Kerajaan Bowontehu. Dalam penelitian ini ada beberapa kekurangan dan perlu ditinjau dalam bentuk perkembangan selanjutnya yang dapat digunakan pada platform lain. Kata kunci : Adobe Fuse, Game 3D, Game Edukasi, Unity 3D